2019
DOI: 10.1177/1474515119886078
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome: voices to be heard

Abstract: This paper is written from the perspective of patients who have been diagnosed with takotsubo syndrome. It seeks to understand why these patients may feel dissatisfied with the care they receive. We consider four factors: (a) takotsubo syndrome is a relatively new condition and the knowledge base about treatment is limited and not widely disseminated among clinicians; (b) the age and gender profile of the patient group; (c) the implications of the categorisation of takotsubo syndrome as ‘broken heart syndrome’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…However, from a nursing person-centered perspective with a holistic approach (Ekman et al, 2011; Santana et al, 2018; Sarvimäki & Stenbock-Hult, 1992), the presentation in manifestations of reason, will, feelings, and needs (Curragh et al, 2020) shows an obviously sensitive and powerless elderly woman whose entire life situation is unmanageable and in complete imbalance (Dahlviken et al, 2015; Sundelin et al, 2020; Wallström et al, 2016a). Accordingly, if no such information exists it is difficult for a cardiac nurse or team to be able to assess what knowledge the person needs and further, to know how to help her understand the situation and make best practice healthcare choices in line with suggested health literacy actions (Mäenpää et al, 2020; Sørensen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, from a nursing person-centered perspective with a holistic approach (Ekman et al, 2011; Santana et al, 2018; Sarvimäki & Stenbock-Hult, 1992), the presentation in manifestations of reason, will, feelings, and needs (Curragh et al, 2020) shows an obviously sensitive and powerless elderly woman whose entire life situation is unmanageable and in complete imbalance (Dahlviken et al, 2015; Sundelin et al, 2020; Wallström et al, 2016a). Accordingly, if no such information exists it is difficult for a cardiac nurse or team to be able to assess what knowledge the person needs and further, to know how to help her understand the situation and make best practice healthcare choices in line with suggested health literacy actions (Mäenpää et al, 2020; Sørensen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the quest to piece together evidence about the pathophysiology and natural history of TTS, the support needs of patients with TTS have largely been overlooked. Women with TTS report feeling dissatisfied and poorly served with the care that they receive [51] and there are many reasons why this is so:…”
Section: Current Patient Education Follow-up Carementioning
confidence: 99%
“…Limited or no follow-up Patients often have limited or no follow-up consultation and further testing after discharge from hospital, and report feeling dismissed and unsupported by the medical profession [51]. There are few options for patients to obtain reliable information and advice about TTS.…”
Section: Current Patient Education Follow-up Carementioning
confidence: 99%
“…With keen interest, I read the article by Curragh and colleagues 1 entitled ‘Takotsubo syndrome: voices to be heard’, which was published in this issue of the European Journal of Cardiovascular Nursing . According to the authors, what is woefully lacking is a patient perspective on the effects of Takotsubo syndrome (TTS) and how care can be improved.…”
mentioning
confidence: 99%
“…We all agree that symptoms are an important aspect of the illness experience and thus can likely have a marked effect on a person’s health-related quality of life. As Curragh and colleagues 1 write, symptoms are also an important issue to consider in patients with TTS. Research on self-reported symptoms affecting patients with TTS needs to be integrated with objective evidence if we hope to engage patients and improve the care process.…”
mentioning
confidence: 99%